Suppression of phagocytic function and phospholipid metabolism in macrophages by phosphatidylinositol liposomes. - Wassef, N M (Proc Natl Acad Sci U S A, 1984)
Increased phagocytosis of complement-opsonized vesicles was accompanied by increased phosphatidylinositol (PtdIns) turnover in murine macrophages. However when PtdIns was also present as one of the lipids in the opsonized liposomes, it reduced both phagocytosis and stimulation of endogenous PtdIns turnover. These suppressive effects did not occur with liposomes containing PtdIns phosphate (PtdIns-P). When a monoclonal IgM "anti-PtdIns-P" antibody that bound to inositol phosphate was substituted for antigalactosyl ceramide antibodies for activating complement in the opsonizing process, enhanced phagocytosis occurred normally but increased cellular PtdIns turnover did not occur. Therefore the data show that, although PtdIns-P cannot replace PtdIns for suppressing PtdIns turnover, PtdIns-P can be induced to be suppressive after specific binding to an antibody that recognizes inositol phosphate. We conclude that ingestion of complement-opsonized liposomes by macrophages and complement-induced turnover of cellular PtdIns are separate but related phenomena that can be independently modulated by the polar group of liposomal PtdIns.